Analisis Tingkat Kepuasan Pengguna dan Tingkat Kepentingan Penerapan SIMUTU Menggunakan Kerangka PIECES - Ahmad Zaky (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Quality Assurance for an organization is a must because the organization that guarantees the quality is an organization that always meet the needs and satisfaction of its customers, because satisfied customers will increase to be loyal customers and this means will provide benefits for the organization concerned. University of Muhammadiyah Malang (UMM) has been using Information System for Quality Assurance designed for evaluation of academic service of University of Muhammadiyah Malang. Students can easily access Quality Management Information System (SIMUTU) anywhere and anytime. Because of the importance of SIMUTU for Quality Assurance of Muhammadiyah University of Malang, this research is conducted to determine whether Quality Management Information System (SIMUTU) has been running properly. In this research, analysis and evaluation of Information System using PIECES Framework analysis model with the purpose of measuring the level of satisfaction and importance level and analyzing the components - components what need to be improved again the quality of the waiter at SIMUTU. From 40 respondents got average result of level of satisfaction 3,53 which mean SIMUTU have give satisfaction to student, meanwhile importance level 3,79 which mean SIMUTU implementation is considered important to improve academic service of University of Muhammadiyah Malang.